2022
DOI: 10.2337/dc23-s016
|View full text |Cite
|
Sign up to set email alerts
|

16. Diabetes Care in the Hospital: Standards of Care in Diabetes—2023

Abstract: The American Diabetes Association (ADA) “Standards of Care in Diabetes” includes the ADA’s current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, a multidisciplinary expert committee, are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed description of ADA standards, statements, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
35

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 152 publications
2
111
0
35
Order By: Relevance
“…Although his blood lactate level (2.9 mmol/L) was slightly higher than the reference value (∼1.8 mmol/L), a marked difference was not observed compared to the previous value of 2.2 mmol/L. Based on these findings, the patient was diagnosed with mild DKA, and continuous intravenous insulin was immediately started in accordance with the standard therapy for DKA ( 8 ). Sodium bicarbonate was also administered to restore acidemia and hyperkalemia ( 9 ).…”
Section: Case Descriptionmentioning
confidence: 82%
“…Although his blood lactate level (2.9 mmol/L) was slightly higher than the reference value (∼1.8 mmol/L), a marked difference was not observed compared to the previous value of 2.2 mmol/L. Based on these findings, the patient was diagnosed with mild DKA, and continuous intravenous insulin was immediately started in accordance with the standard therapy for DKA ( 8 ). Sodium bicarbonate was also administered to restore acidemia and hyperkalemia ( 9 ).…”
Section: Case Descriptionmentioning
confidence: 82%
“…Although the American Diabetes Association 46 and the CDC 23 recommend that perioperative clinicians should avoid marked hyperglycemia and hypoglycemia, they lack consensus on the target maintenance threshold. The American Diabetes Association recommends a target blood glucose range between 80 and 180 mg/dL during the perioperative period 46 . However, the CDC recommends maintaining perioperative blood glucose levels less than 200 mg/dL regardless of the patient's diabetic status 23 .…”
Section: Evidence‐based Best Practices For Preventing Ssismentioning
confidence: 99%
“…45 The odds ratios for a group of complications that included wound infection and sepsis were 1.68 (95% confidence interval [CI] = 1.15 to 2.44) for patients with a blood glucose between 140 and 180 mg/dL and 3.46 (95% CI = 2.24 to 5.36) for patients with a blood glucose greater than 180 mg/dL. 45 Although the American Diabetes Association 46 and the CDC 23 recommend that perioperative clinicians should avoid marked hyperglycemia and hypoglycemia, they lack consensus on the target maintenance threshold. The American Diabetes Association recommends a target blood glucose range between 80 and 180 mg/dL during the perioperative period.…”
Section: Perioperative Glucose Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…[5•, 6•, 10, 19•, 21, 22, 28] Time in range (70-180 mg/dl), was reported in 5 studies and fell within a wide range of 46.1% and 75.7%. [4•, 5•, 17, 19•, 30] In one study, time in range was reported as 144-180 mg/dl to better align with American Diabetes Association in hospital recommendations for critical care [31] and found significantly higher time between 144 and 180 mg/dl for participants on CGM vs. standard POC blood glucose monitoring (BGM) ((51.5% vs 29.0%). [16] One study reported similar accuracy (60.1% vs. 57%, in zone A of the Clark Error Grid, respectively) between CGM placement sites (thigh vs. abdomen).…”
Section: Clinical and Implementation Outcomesmentioning
confidence: 99%